The combination of tezacaftor and ivacaftor in the treatment of patients with cystic fibrosis: clinical evidence and future prospects in cystic fibrosis therapy - Lommatzsch, Sherstin T. (Ther Adv Respir Dis, 2019)
Years of tremendous study have dawned a new era for the treatment of cystic fibrosis (CF). For years CF care was rooted in the management of organ dysfunction resulting from the mal-effects of absent anion transport through the CF transmembrane regulator (CFTR) protein. CFTR, an adenosine triphosphate binding anion channel, has multiple functions, but primarily regulates the movement of chloride anions, thiocyanate and bicarbonate across luminal cell membranes. Additional roles include effects on other electrolyte channels such as the epithelial sodium channel (ENaC) and on pulmonary innate immunity. Inappropriate luminal anion movement leads to elevated sweat chloride concentrations, dehydrated airway surface liquid, overall viscous mucous production, and inspissated bile and pancreatic secretions. As a result, patients develop the well-known CF symptoms and disease-defining complications such as chronic cough, oily stools, recurrent pulmonary infections, bronchiectasis, chronic sinusitis and malnutrition. Traditionally, CF has been symptomatically managed, but over the past 6 years those with CF have been offered a new mode of therapy; CFTR protein modulation. These medications affect the basic defect in CF: abnormal CFTR function. Ivacaftor, approved for use in the United States in 2012, is the first medication in CF history to improve CFTR function at the molecular level. Its study and approval were followed by two additional CFTR modulators, lumacaftor/ivacaftor and tezacaftor/ivacaftor. To effectively use currently available CF therapies, clinicians should be familiar with the side effects of the drugs and their impacts on patient outcomes. As many new modulators are on the horizon, this information will equip providers to discuss the benefits and shortcomings of modulator therapy especially in the context of limited healthcare resources.